الْجُزْءُ فِيهِ مِنْ حَدِيثِ أَبِي الْقَاسِمِ إِسْمَاعِيلَ بْنِ الْقَاسِمِ بْنِ إِسْمَاعِيلَ الْحَلَبِيِّ ، عَنْ شُيُوخِهِ تحقيقُ ودراسةُ - عبد الرحمن السيد السيد عبدالغفار بلح (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2022)
This study dealt with an investigation of an important recent part: "The part in which abu al-Qasim Ismail bin Al Qasim bin Ismail al-Halabi, about his elders", and his article of hadiths, antiquities, and poems, in which the owner of the part collected a number of different conversations, effects and poems about his elders, and does not specialize in a particular topic, or a particular issue, and most of his speeches are supported, it is important for the modern parts of the importance of not hiding the student of hadith, and the part included sixty-four modern And as a effectIn his research, the researcher walked on the descriptive, critical analytical inductive approach, the research plan: the research consists of two chapters preceded by an introduction, followed by a conclusion, presented: presented at the beginning of the investigation an introduction in which it indicated a party of the efforts of scientists in the service of hadith, the importance of modern parts and benefits after i knew about it, and the research plan, Chapter 1: The study includes three investigations: the first research: dealing with a study on the owner of the part, the second research: the definition of the novels of the part, the third research: the introduction of the manuscript, chapter two and there is one research: the text achieved and i have resorted to these texts and attributed them to their part of the books of the people of science assigned, the conclusion: and in it the results of the research, and its importance comes out to join other modern parts